'TAVR Infected Pseudomonas Endocarditis': a case report. (November 2022) - Essien, Francis; Patterson, Shane; Estrada, Fernando; Wall, Timothy; Madden, John; McGarvey, Michael
Pseudomonas aeruginosa ( P. aeruginosa ) rarely causes infective endocarditis (IE), previously reported for approximately 3% of all patients with IE. 1 Most commonly, the infection occurs in intravenous drug users (IVDU) as right-sided endocarditis, noting presentations of P. aeruginosa IE without history of intravenous drug to be extremely rare, finding only a few cases reported in the literature. However there are increasing reports of cardiovascular implantable electronic device–related and prosthetic heart valve infections caused by this pathogen in non-IVDUs. 2 This report will focus on the clinical presentation, management, and outcome of P. aeruginosa endocarditis in an 89-year-old patient with a transcatheter aortic valve replacement (TAVR). Medical management was pursued due to the patient's underlying comorbidities. Long-term suppressive antibiotic therapy with delafloxacin was successful in maintaining negative blood cultures, despite an allergy to levofloxacin and ciprofloxacin. Plain Language Summary: An 89-year-old male was admitted to our hospital after he was diagnosed with a blood stream infection. The initial identification noted gram-negative organisms consistent with Pseudomonas Aeruginosa so the patient was started on intravenous (IV) antibiotics. He improved after the antibiotics started and was discharged to a nursing facility to complete his antibiotics course. While at the facility, after he had finished his antibiotics, he started to become ill again. He was brought back to the hospital to be evaluated. His repeat blood cultures again grew P. Aeruginosa. This suggested that his infection had not been cleared the first time and most likely he had a source of bacterial growth. A few years prior, a transcatheter aortic valve replacement (TAVR) had been performed for the patient. This was suspected as the source of continued infection and so a transthoracic echocardiogram was obtained, which revealed vegetation on the TAVR. We also obtained a magnetic resonance imaging (MRI) of the brain, which demonstrated infarcts of several portions of the brain consistent with emboli. Due to his age and additional medical issues, the patient was not a candidate for surgical valve replacement. We decided to try medical therapy with a fluoroquinolone antibiotic since the bacteria was susceptible to it. Unfortunately, he had demonstrated allergies to the usual choices to include Levaquin and ciprofloxacin. Therefore, we elected to start him on a new fluoroquinolone agent that had recently been FDA approved and obtained by our facility called delafloxacin. The patient tolerated this well and his repeat blood cultures remain clear. After discussion with the infectious disease specialist, he requires a lifelong suppression with the medication since the TAVR cannot be removed. This case is meant to illustrate the effectiveness of medical therapy when surgical options are not available.